2017
DOI: 10.1186/s12862-017-0973-4
|View full text |Cite|
|
Sign up to set email alerts
|

Phylogenomic analyses of Crassiclitellata support major Northern and Southern Hemisphere clades and a Pangaean origin for earthworms

Abstract: BackgroundEarthworms (Crassiclitellata) are a diverse group of annelids of substantial ecological and economic importance. Earthworms are primarily terrestrial infaunal animals, and as such are probably rather poor natural dispersers. Therefore, the near global distribution of earthworms reflects an old and likely complex evolutionary history. Despite a long-standing interest in Crassiclitellata, relationships among and within major clades remain unresolved.MethodsIn this study, we evaluate crassiclitellate ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 74 publications
(91 reference statements)
1
22
0
Order By: Relevance
“…Recent molecular analyses based on transcriptome data have shown that representatives of the Haplotaxidae sensu lato (i.e., Haplotaxis gordioides , Delaya leruthi , and Pelodrilus sp.) comprised the sister group of Metagynophora (Crassiclitellata + Moniligastridae) (Anderson et al, 2017). When more exhaustive taxonomic sampling was considered, Haplotaxidae appeared as non‐monophyletic, Pelodrilus sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent molecular analyses based on transcriptome data have shown that representatives of the Haplotaxidae sensu lato (i.e., Haplotaxis gordioides , Delaya leruthi , and Pelodrilus sp.) comprised the sister group of Metagynophora (Crassiclitellata + Moniligastridae) (Anderson et al, 2017). When more exhaustive taxonomic sampling was considered, Haplotaxidae appeared as non‐monophyletic, Pelodrilus sp.…”
Section: Discussionmentioning
confidence: 99%
“…More recent molecular analyses confirmed that Haplotaxidae are the closest relatives to Crassiclitellata, although as a paraphyletic assemblage (Anderson et al, 2017;Martinez-Ansemil, Creuzé Des Châtelliers, Martin, & Sambugar, 2012). Finally, a broad phylogenetic assessment based on transcriptomic genetic data (Erséus et al, 2020) showed that haplotaxids are not monophyletic and that some of them cluster either with Crassiclitellata or Moniligastridae (earthworm-sized terrestrial non-crassiclitellates).…”
mentioning
confidence: 97%
“…Number of species are from Sket and Trontelj (), Williams, Gelder, Proctor, and Coltman (), Anderson et al. () or estimated from Reynolds and Wetzel (). Also shown are the species from each lineage used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…After publication of the original article [ 1 ], the authors received the correct museum catalogue number of Avelona ligra , Lumbricidae, which is listed in Table 1 . The museum number currently reads MNHN XXXXXX in the original article, but should read MNHN HEL593.…”
Section: Erratummentioning
confidence: 99%